2019
DOI: 10.1016/j.cmet.2018.09.020
|View full text |Cite
|
Sign up to set email alerts
|

TLR8-Mediated Metabolic Control of Human Treg Function: A Mechanistic Target for Cancer Immunotherapy

Abstract: Regulatory T (Treg) cells induce an immunosuppressive microenvironment that is a major obstacle for successful tumor immunotherapy. Dissecting the regulatory mechanisms between energy metabolism and functionality in Treg cells will provide insight toward developing novel immunotherapies against cancer. Here we report that human naturally occurring and tumor-associated Treg cells exhibit distinct metabolic profiles with selectivity for glucose metabolism compared with effector T cells. Treg-mediated accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
196
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(204 citation statements)
references
References 77 publications
(203 reference statements)
6
196
2
Order By: Relevance
“…3B). Similar result was observed in the immunecompetent EMT6 mouse syngeneic breast cancer model in which DN052 markedly 19 suppressed tumor growth as a single agent and resulted in complete tumor regression in 1/8, 2/8 and 3/8 tumor-bearing mice at 40, 80 and 160 mg/kg, respectively (Fig. 3C, 3D).…”
Section: Dn052 Strongly Inhibited Tumor Growth As a Single Agent Or Isupporting
confidence: 85%
See 2 more Smart Citations
“…3B). Similar result was observed in the immunecompetent EMT6 mouse syngeneic breast cancer model in which DN052 markedly 19 suppressed tumor growth as a single agent and resulted in complete tumor regression in 1/8, 2/8 and 3/8 tumor-bearing mice at 40, 80 and 160 mg/kg, respectively (Fig. 3C, 3D).…”
Section: Dn052 Strongly Inhibited Tumor Growth As a Single Agent Or Isupporting
confidence: 85%
“…TLR8 was chosen because it is one of the most important molecules of the innate immunity (42,(44)(45)(46). Accumulating evidence indicated that activation of TLR8 could reverse Treg and MDSC mediated immune suppression resulting in strong tumor inhibition (16,(19)(20)(21). One of the major causes of cancer immunotherapy failure is potent suppression of immune response by Treg or MDSC cells (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR8 stimulation with poly-G reversed the ability of regulatory T cells to suppress T cell proliferation 40 , whereas stimulation with the TLR7/8 ligand R848 in conjunction with TCR activation enhanced proliferation, IFN-γ, IL-8, and IL-10 secretion in memory CD4+ T cells 39 . A recent study reported TLR8-mediated reversal of Treg suppressive functions through inhibition of glucose uptake and glycolysis 96 . Our data show that TLR8 and TLR7 stimulation enhanced TCR activation by increasing the level of phosphorylated proteins involved in TCR signaling such as ribosomal protein S6 and, MAPK signaling (p38, ERK1/2) and NFκB p65.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple murine tumour models, TI‐Tregs have proven to be less vulnerable to glucose restriction than other effector T‐cells . However, in some settings, inhibition of glycolysis in TI‐Tregs reversed Treg suppressive function and promoted anti‐tumour immunity . This may be due to the capacity of Tregs to preferentially convert pyruvate into mitochondrial acetyl‐CoA, which would further support OXPHOS but, more likely, this reflects a requirement for some glycolytic activity in Tregs despite their increased utilization of OXPHOS compared with effector T‐cells.…”
Section: Metabolism In Ti‐tregsmentioning
confidence: 99%